Penyalahgunaan Obat Psikofarmaka dan Dampaknya terhadap Kesehatan Mental Remaja di Sekolah Menengah Atas (SMA) - Syifa’, Nailis; Aprilia, Galuh; Risqi, Iin Hiqmathul; Agustin, Nesha Elcyra; Mirza, Mazaya Febinazhira; Hasan, Qurrotul Aini; Safitriana, Laela Jelita; Fikriyah, Izzatul; Fazha, Nurliva Maulidya; Syafira, Kholifah; Aulia, Nazhirah Rahma (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
High school students often experience pressures that affect their mental health due to unstable personalities. The negative effects of poorly managed mental health can impact their development. Therefore, early education on the abuse of psychopharmaceutical drugs and its impact on adolescent mental health is essential. The specific target of this counseling activity was to enhance the understanding of students at Muhammadiyah 3 Batu High School. The method used involved delivering materials and explanations through a PowerPoint presentation and the